A comparative study on the formation of Sinoxenic person nouns in Korean, Chinese, Japanese, and Vietnamese. (March 2021) - Jiyoung, Lee
This study attempts to sketch out how Korean, Chinese, Japanese, and Vietnamese (hereafter K, C, J, and V, respectively) have produced Sinoxenic personal nouns. The formation of Sinoxenic personal noun falls into one of three types: (1) with an affix attached to the original word; (2) semantic expansion; (3) expansion to figurative meanings. One observes all three types throughout KCJV; however, specific patterns differ slightly between Vietnamese and the other three languages. The differences between Vietnamese and the other three in Sinoxenic formation result from differences in geographical distances and frequencies of linguistic exchanges. Meanings of Sinoxenic words stayed similar among Korea, China, and Japan, due to frequent human and literary exchanges, which did not occur between Vietnam and the other three countries.